1998
DOI: 10.1161/01.cir.98.12.1164
|View full text |Cite
|
Sign up to set email alerts
|

Activated Platelets Induce Monocyte Chemotactic Protein-1 Secretion and Surface Expression of Intercellular Adhesion Molecule-1 on Endothelial Cells

Abstract: The present study indicates that activated platelets modulate chemotactic (MCP-1) and adhesive (ICAM-1) properties of endothelial cells via an NF-kappaB-dependent mechanism. Platelet-induced activation of the NF-kappaB system might contribute to early inflammatory events in atherogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
181
2
20

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(209 citation statements)
references
References 47 publications
(54 reference statements)
6
181
2
20
Order By: Relevance
“…Accordingly in our previous study, which examined the interaction between monocytes and MC, both cell-to-cell contact and soluble factors were required for the maximum activation of the latter (18). Other studies have shown that platelet contact induces chemokine or adhesion molecule expression by endothelial cells or leukocytes through NF-B activation (10,12). NF-B plays a critical role in inflammatory response through induction of a variety of proinflammatory genes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly in our previous study, which examined the interaction between monocytes and MC, both cell-to-cell contact and soluble factors were required for the maximum activation of the latter (18). Other studies have shown that platelet contact induces chemokine or adhesion molecule expression by endothelial cells or leukocytes through NF-B activation (10,12). NF-B plays a critical role in inflammatory response through induction of a variety of proinflammatory genes.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Blocking nuclear factor-B activity in endothelial cells by anti-sense oligonucleotides will affect not only ICAM-1 upregulation but also MCP-1 production and, ultimately, the homing of monocytes. 34 Adhesion and transmigration, mediated by several interacting molecular mechanisms, appear to be essential for monocyte traffic in atherosclerosis. Some of these factors, such as nuclear factor-b, MCP-1, interleukin-8/neutrophil-activating peptide, plateletactivating factor, and RANTES, may be activated or upregulated at an early stage in apoE Ϫ/Ϫ but not wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The endothelial cells seem a likely candidate, because they first receive the impact of acute hyperglycemia, which may reduce NO availability. 19 Further support for this hypothesis comes from the results of a recent study that shows that ADP-activated platelets induce surface expression of ICAM-1 in cultured endothelial cells 22 : an additional effect of acute hyperglycemia in humans is to increase platelet aggregation in response to stimulants such as ADP, which, according to Grawaz et al, 22 may contribute to the elevation of plasma sICAM-1 levels. Last, the increased plasma sICAM-1 levels seen after an oral glucose challenge in humans is completely prevented by the administration of the antioxidant glutathione, 13 pointing to an important role for oxidative stress in mediation of the effects of hyperglycemia on sICAM-1 levels.…”
Section: Marfella Et Al Circulating Adhesion Molecules In Humansmentioning
confidence: 97%